Pembinaan Karakter Perangkat Desa dalam Pelayanan Publik - Alifia Cahyani Kurnia Sanjaya (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2023)
Optimal service in administering government is a real manifestation of creating good governance. Providing services to the community is also a real work result in government, especially village government. Thus, good and correct governance is needed to produce quality services. Based on Law Number 6 of 2014 concerning Villages, forming a village government that is professional, efficient, effective, open and accountable is inseparable from optimal public services in administering village governance. Improving public services in village government can be done with good governance and implementing programs that can support the performance of village officials in serving the community. This study aims to foster the character of village officials in public services in Gombong Village, Panimbang District, Pandeglang Regency, Banten. Governance carried out by the Gombong village government is inseparable from the results of good leadership so that it can manage and regulate a good village governance system. The results of this activity can be said to be successful with the presence of government officials from Gombong Village, Panimbang District, Pandeglang Regency, Banten. This can be seen from the percentage of participant attendance and enthusiasm during the activity.